Fine Mapping and Characterization of an Aphid-Resistance Gene in the Soybean Landrace Fangzheng Moshidou - Yang, Jing; Liu, Guangyang; Tang, Junyong; Wang, Xiujun; Diao, Yanling; Su, Yang; Sun, Dan; Shang, Jiawei; Guo, Yong; Qiu, Li-Juan (Frontiers in Plant Science, 2022)
The soybean aphid poses a severe threat to soybean quality and yield by sucking phloem sap and transmitting plant viruses. An early-maturing and highly resistant soybean landrace, Fangzheng Moshidou, with markedly reduced aphid colonization has been identified by screening of aphid-resistant soybean accessions. In a population derived from the cross of Fangzheng Moshidou with the susceptible cultivar Beifeng 9, resistance was conferred by a single dominant gene. Three linked markers, Satt114, Satt334, and Sct_033, on chromosome 13 were identified by bulked-segregant analysis. Additional simple-sequence repeat and single-nucleotide polymorphism (SNP) markers were developed for gene mapping. The resistance of Fangzheng Moshidou was fine-mapped to the interval between the SNP markers YCSNP20 and YCSNP80, corresponding to 152.8 kb in the Williams 82 assembly 2 genome. This region was near the reported loci Rag2 and Rag5 but did not overlap the interval containing them. A unique haplotype is described for Fangzheng Moshidou that distinguishes it from soybean accessions PI 587972, PI 594879, and PI 567301B in the interval containing Rag2 and Rag5. These results indicate that Fangzheng Moshidou harbors a novel gene at a tightly linked resistance locus, designated as RagFMD. Fourteen candidate genes were annotated in the fine-mapping region, including seven NBS-LRR genes, which are usually considered resistance genes in plant defense. Most of these candidate genes showed variations distinguishing the resistant and susceptible parents and some genes also showed differences in expression between the two parental lines and at several times after aphid infestation. Isolation of RagFMD would advance the study of molecular mechanisms of soybean aphid resistance and contribute to precise selection of resistant soybeans.